Investigation of explants sterilization process, effect of light intensity and concentration of agar for callus induction of Kappaphycus alvarezii (Doty) doty (Rhodophyta) in vitro - Mơ, Vũ Thị; Reddy, CRK (Vietnam Journal of Biotechnology, 2016)
Objective of this study was to ascertain the optimum condition for callus induction of K. alvarezii (Doty) in vitro such as to determine the explants sterilization process, the effect of intensity of light and the concentration of agar. Fresh thalli treated with 0.5% - 1% detergent for 5 mins followed by 0.5% - 1% betadine for 2 – 3 mins and incubated with 0.5% - 1% broad spectrum antibiotic mixture in PES medium for 1 day produced 95 – 98% bacteria free healthy explants.  Two independent experiments with light intensity and agar contentration of the environment were carried out at 5 different levels of 0, 5, 25, 50, 70 µmol photon.m2.s-1 and 9 agar concentrations of 0.5%, 0.75%; 1.0%, 1.25%, 1.5%, 1.75%, 2.0%, 2.5%, 3.0%. The highest callus induction rate was (96 ± 3.5 – 98 ± 2.1%) at 5 - 25 µmol photon.m-2.s-1 and (87 ± 5.8% – 90 ± 5.0%) in 1% - 3% agar concentration after 2 weeks of explants. The highest callus living rate was 98% at the light intensity of 25 µmol photon.m-2.s-1 and (75 ± 5.7 – 84 ± 1.1%) in 0.75 – 1.5% agar concentration after 2 months of explants. The highest callus re-induction rate was 50 – 55% at the light intensity of 5 – 25 µmol photon.m-2.s-1 and 60 – 65% in 1 – 1.5% agar concentration. Callus was not observed in dark condition (0 µmol photon.m-2.s-1). These calluses, that were strong, big and had filamentous type, will be a good material for the next production stage of embryonic callus production and seedling regeneration from micropropagules